Democratic Principal (Kula Babong) Leadership Model: Examining the Role of Du'a Moan Watu Pitu in Sikka Krowe Community: Model Kepemimpinan Kepala Sekolah Demokratis (Kula Babong): Mengkaji Peran Dua Moan Watu Pitu (Lembaga Pemangku Adat) Masyarakat Sikka Krowe - Nuwa, Gisela; Nasa, Rikardus (Universitas Muhammadiyah Sidoarjo, 2022)
Preserving culture is an important aspect of the life of indigenous peoples because it is identical to a lifestyle that is still guided by local customs. The process of cultural preservation in indigenous peoples cannot be separated from the important role of the community as an academic locus and Du'a Mo'an Watu Pitu as the responsible one. Based on this reality, this study aims to determine the leadership model of a democratic school principal based on local wisdom and examine the role of du'a moan watu pitu in maintaining the Kula babong culture (democracy) in the Sikka Krowe community. The research method used in this research is descriptive qualitative with an ethnographic approach. The subjects in this study were 4 principals of private and public schools, four Sikka krowe traditional leaders who inhabit each region, and culturalists in the Krowe Ethnic community, Sikka krowe Regency, East Nusa Tenggara. Data collection techniques used are observation, interviews and documentation. The results showed that the school principal's leadership model was based on the values of Sikka Krowe's local wisdom: the value of honesty, the value of courage, the value of kula babong, and charisma. Du'a Mo'an Watu Pitu's role in preserving the Kula Babong culture (democracy) is to maintain the integrity of traditional institutions, perform traditional rituals, resolve social conflicts and uphold justice.